APPLICATION OF SELECTED DEBT RATIOS ON SLOVAK AGRICULTRURE - Jana Prevužňáková; Tomáš Rábek; Peter Serenčéš (Polityki Europejskie, Finanse i Marketing, 2013)
The company can be funded from a variety of sources such as foreign or own capital. This article will be devoted to the analysis of foreign sources of funding in the agricultural sector for selected years while specific ratios have been selected. Ratio of debt is in general a ratio of outputs of each balance sheet and profit and loss statement of a company with the regard to the items which are characterizing the actual debt. Based on it is possible to monitor and analyze the financial resources of the company. Hence it is the ratio of equity and foreign capital in the business, while this situation has of course an impact on corporate financial stability, but also on the return on equity, debt or credit. For the purposes of developing this article it has been worked with the data of Slovak agriculture companies in the chosen period of 2004- 2011. We assume that farms will use the optimal proportion of debt and equity capital.